PENATALAKSAAN HOLISTIK PADA WANITA PENGRAJIN ANYAMAN LANSIA 62 TAHUN DENGAN OSTEOARTHRITIS DAN ASMA INTERMITEN DI PUSKESMAS KAMPUNG SAWAH MELALUI PENDEKATAN KEDOKTERAN KELUARGA - ayu agustira; Ta Larasati (Medula, 2022)
Osteoarthritis (OA) is a degenerative disease of the joints that involves the cartilage, joint lining, ligaments and bones causing pain and stiffness in the joints. The causes of osteoarthritis are multifactorial, including gender, obesity, genetic factors, race, family history, joint injury, strenuous physical activity, work, and repetitive movements of the same joints. Asthma is a chronic respiratory disease based on chronic inflammation which results in obstruction and hyperreaction of the respiratory tract as a result of the interaction between genetic, host, and environmental factors. Both osteoarthritis and hypertension are diseases that must be managed comprehensively because they are chronic.To apply the principles of family doctor medicine according to the problems found in patients in various aspects and carry out a holistic and comprehensive management that includes patient-centered, family approached, and community-oriented based on evidence-based medicine. Patient Mrs. I, 62  years, with complaints of knee pain since about 5 day ago. Knee pain is felt especially when the patient does strenuous activities or when in a squatting position and then stands up, and when the patient goes up and down stairs, but the complaint improves when the patient rests.  The patient was diagnosed with osteoarthritis.  The patient has a history of asthma since childhood and asked for asthma medication because he was worried that in the rainy season with cold weather his asthma could recur. Several factors can affect the patient's condition, namely internal and external risk factors. In this case, diagnosis and treatment have been carried out according to the latest theory and journals. After the intervention, there was a decrease in clinical symptoms and an increase in the knowledge of patients and their families.